Population development of the invader ctenophore Mnemiopsis leidyi , in the Black Sea and in other seas of the Mediterranean basin - Shiganova, T A; Mirzoyan, Z A; Studenikina, E A; Volovik, S P (Marine biology, 2001)
In the last two decades of the twentieth century, the ctenophore Mnemiopsis leidyi (A. Agassiz) has invaded the Black, Azov, Marmara and Aegean Seas, and, recently, the Caspian Sea. Here, we compare its spatial and temporal distribution, seasonal dynamics and the time and duration of reproduction.